Epigenetic Regulation of Hepatic Stellate Cell Activation and Macrophage in Chronic Liver Inflammation - Shi, Chun-xia; Wang, Yao; Jiao, Fang-zhou; Chen, Qian; Cao, Pan; Pei, Mao-hua; Zhang, Lu-yi; Guo, Jin; Deng, Wei; Wang, Lu-wen; Gong, Zuo-jiong (Frontiers in Physiology, 2021)
Chronic liver inflammation is a complex pathological process under different stress conditions, and the roles of stellate cells and macrophages in chronic liver inflammation have been widely reported. Moderate liver inflammation can protect the liver from damage and facilitate the recovery of liver injury. However, an inflammatory response that is too intense can result in massive death of hepatocytes, which leads to irreversible damage to the liver parenchyma. Epigenetic regulation plays a key part in liver inflammation. This study reviews the regulation of epigenetics on stellate cells and macrophages to explore the new mechanisms of epigenetics on liver inflammation and provide new ideas for the treatment of liver disease.